2017
DOI: 10.21834/e-bpj.v2i5.680
|View full text |Cite
|
Sign up to set email alerts
|

Discord in the Family Environment: Reviewing incidences of fratricide and sororicide in Malaysia

Abstract: Family discords or quarrels are considered normal and ordinary. However, the level and intensity of the discords and disputes have led to incidences of fratricide and sororicide. In the case of fratricide (the killing of one's brother) and sororicide (the killing of one's sister), the escalating number of incidences as reported in the media requires proper intervention by the relevant parties. The aim of this paper is to review published articles on family discords and violence, particularly on incidences of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Of these, 32 (80%) were fratricides while eight (20%) were sororicides. For Malaysia, Hashim et al (2017) found similar evidence of a low prevalence of sororicide, noting that “the occurrence of sororicide is scarce” and that “most of the sibling violence cases and killings involved the male sibling [as victim] or fratricide” (p. 51). Many past researchers have attributed the paucity of research on siblicide to the infrequency of the offense.…”
Section: Review Of the Literaturementioning
confidence: 88%
See 4 more Smart Citations
“…Of these, 32 (80%) were fratricides while eight (20%) were sororicides. For Malaysia, Hashim et al (2017) found similar evidence of a low prevalence of sororicide, noting that “the occurrence of sororicide is scarce” and that “most of the sibling violence cases and killings involved the male sibling [as victim] or fratricide” (p. 51). Many past researchers have attributed the paucity of research on siblicide to the infrequency of the offense.…”
Section: Review Of the Literaturementioning
confidence: 88%
“…As noted earlier, much of the scant extant research on sororicide has been conducted in Western industrialized societies (Adam & Livingston, 1993; Ewing, 1997; Peck & Heide, 2012). While there have been a very small number of published works on sororicide cases in the Middle East and Southeast Asia (Hashim, Ahmad, Zulkifli, & Bahrin, 2017), to the best of the current authors’ knowledge, to date there has been no empirical analysis of sororicide incidents in an African, South Pacific, or South American society. Indeed, our literature search yielded only one recently published study on sororicide in an Asian society (see Hashim et al, 2017).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 3 more Smart Citations